The Role of Emotional Intelligence and Social Support: Predicting The Students' Learning Achievement Improvement - Mujidin Mujidin; Ajeng Rizky Ardhia Pramesti; Husnul Khotimah Rustam (Universitas Ahmad Dahlan, 2021)
The purpose of this study was to determine the role of emotional intelligence and social support with learning achievement in class XI students of SMA Negeri 1 Bengkulu Selatan. This study is a non-experimental study with a correlational design to determine the effect of emotion regulation on students' learning achievement. This study proves two hypotheses, first, there is a significant emotional intelligence with an increase in student achievement. Second, there is a significant relationship between social support and an increase in student achievement. This study collected data from 89 students using a random technique from the population of SMA Negeri 1 Bengkulu Selatan. The data collection instruments used were emotional intelligence questionnaires, social support questionnaires and student achievement documents. The analysis used is more specific, namely simple linear regression analysis. The results showed that there was a significant relationship between emotional intelligence and academic achievement with an rxy value of 0.283 plus a p value of 0.013. Furthermore, second hypotheses, there is a significant relationship between social support and an increase in student achievement was rejected with a p value of 0.064 and clarified with an rxy value of 0.212, which means that there is no relationship between social support and increased learning achievement. The results of this study can be used as a reference to determine the right way to deal with students' academic and problems with guidance and counseling that is fun to maximize emotional intelligence, social support and student achievement.